PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, OPINI AUDIT, DAN PENGHINDARAN PAJAK TERHADAP PENERBITAN LAPORAN AUDIT - Jessica Ovelia Niocolas; Lukman Lukman (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2022)
The purpose of this study was to investigate the effect of using accounting information on business success. This study also investigates the effect of venture capital on business success. This study uses a survey method conducted by collecting questionnaires for MSME actors in Makassar City. Data analysis in this study using multiple regression method and sample selection using Random Sampling method with a total sample of 94 respondents. The results of this study indicate that the use of accounting information has a significant positive effect on business success. The influence of venture capital also has a positive effect on business success. In short, the use of accounting information and venture capital fully has an influence on business success.